The Effect of Tangibles, Reliability, Responsiveness, Assurance, and Empathy Aspects on Hospitalization Services in Hospitals on Patient Satisfaction - Fachri, Muhammad (Greenation Publisher & Yayasan Global Research National, 2024)
One of the health services that has a very important role in providing health services to the community is the hospital. The existence of hospitals as health care institutions is regulated in Law No.44 of 2009. Hospitals play an important role in the health care system and are health care institutions that have an organized staff of medical professionals, and inpatient facilities, by providing medical, nursing and related services 24 hours per day, 7 days per week and providing complete health services to the community, both curative and preventive. In addition, the hospital also serves as a place of education for health workers and a place of research. Good health services provide effective, safe, and high-quality services to those who need them supported by adequate resources (WHO, 2014). From field observations and literature studies based on observations, there are several problems as follows: Poor tangibles aspects of service quality affect inpatient satisfaction at WALED Hospital, Cirebon Regency. Poor reliability aspects of service quality affect inpatient satisfaction at WALED Hospital, Cirebon Regency Poor responsiveness aspects of service quality affect inpatient satisfaction at WALED Hospital, Cirebon Regency Poor assurance aspects of service quality affect inpatient satisfaction at WALED Hospital, Cirebon Regency Poor Empathy aspects of service quality affect inpatient satisfaction at WALED Hospital, Cirebon Regency.